Inter-religious Harmony Between Hindu and Muslim Religious Communities of Miya Patan of Pokhara - Ojha, Niranjan (Janapriya Journal of Interdisciplinary Studies, 2022)
Most Hindus see Muslims as the opposing faith to their own, although Hindus attend Muslim celebrations and Muslims attend Hindu festivals in Pokhara. Muslims in Pokhara dress in Nepali attire, which is not Islamic, and communicate in Nepali rather than Urdu or Hindi, which are peculiar to Muslim fundamentalism. Religious harmony is always vital for maintaining peace and harmony in a multi-religious country like Nepal. Despite the fact that Nepal is a secular country with a Hindu majority, Muslims are important and integral parts of Nepalese society. Unlike neighboring nations, there have been no severe religious riots or confrontations between Hindus and Muslims up to this point. When two cultures meet and interact, religious ideas will be transferred. The Muslims of Miya Patan have never contemplated a separate identity or attempted to break from society. They are quite proud of their national identity and identify more as Nepalese than Muslims. For ages, the Muslims of Pokhara have coexisted peacefully with their Hindu neighbors. This study attempts to explain the underlying causes influencing religious harmony in a multi-religious community of Miya Patan of Pokhara. In order to address the problem of study, discussion, in-depth interview and library research methods are applied. It is based on qualitative research method. It underlines the importance of components responsible for religious harmony in Pokhara. The findings may inspire other minority religious groups to maintain solid relationships in different parts of the country.